Impact of Social Capital on the Process of Commercialisation of Knowledge in an Organisation Влияние социального капитала на процесс коммерциализации знания в организации - Koba Nataliya V. (Bìznes Inform, 2013)
The goal of the article lies in identification of the essence of social capital, understanding its structure, forms and features and study its role and influence upon the process of commercialisation of knowledge in an organisation. Having analysed the “social capital” notions from existing scientific literature, the article specifies its essence. Having analysed and systemised theoretical provisions of various researchers, the article provides a structure of social capital, specifies its main forms, types, common and distinguishing features with respect to other types of capital of an organisation. Having generalised results of studies of foreign scientists, the article identifies influence of social capital upon the process of transformation of knowledge in an organisation. Using example of project organisations of the gas industry of Ukraine, the article analyses the outer contour of the social capital, in the result of which it establishes direct impact of social capital on commercialisation of knowledge in these organisations. The article grounds a necessity of ensuring the positive character of this influence by modern organisations. Development of theoretical and methodical provisions and practical recommendations on managing the social capital of organisations as a decisive factor of ensuring commercialisation of their knowledge are considered to be priority directions of studies. Цель статьи заключается в определении сущности социального капитала, выявлении его структуры, форм и черт, а также изучении его роли и влияния на процесс коммерциализации знания в организации. В результате анализа существующих в научных трудах дефиниций понятия «социальный капитал» в статье уточнена его сущность. Анализируя и систематизируя теоретические положения различных исследователей, была представлена структура социального капитала, выделены его основные формы, виды, общие и отличительные черты по отношению к другим видам капитала организации. На основании обобщения результатов исследований зарубежных ученых определено влияние социального капитала на процесс трансформации знания в организации. На примере проектных организаций газовой промышленности Украины проанализирован внешний контур социального капитала, в результате чего установлено непосредственное влияние социального капитала на коммерциализацию знаний в этих организациях. Обоснована необходимость обеспечения положительного характера этого влияния современными организациями. Актуальными и приоритетными направлениями исследований является разработка теоретико-методических положений и практических рекомендаций по управлению социальным капиталом организаций как решающим фактором обеспечения коммерциализации их знаний.